A experiência de consumidores(as) idosos(as) nos aplicativos bancários - Mizael, Luciane de Farias (2023)
The elderly, in 2040, will represent 1/4 of the Brazilian population (IBGE, 2023). It is important to note that, in 25% of Brazilian households, retired people are responsible for the family (IBGE, 2017). This situation makes the decision to consume banking products extremely relevant (FRANÇA, 2011). This public, in general, accesses the internet and applications when making financial transactions almost daily. Even so, it is not uncommon for many users to report difficulties with banking applications (FEBRABAN, 2022). Given this scenario, this study's main objective is to understand the experience of elderly people as users of banking applications (mobile banking), using an exploratory methodology with a qualitative phenomenological approach. Data collection was carried out via snowball (consecutive indications), through 11 interviews (10 women and 1 man), aged between 60 and 75 years and with the aid of a semi-structured script with 30 questions. At the end of the study, it was possible to understand that security is the main barrier and determining factor in using the application, and the great facilitator is family support and bank employees, who help with the entry into the application and its main functions. In this way, and in view of the lessons learned, it is possible to suggest guidelines for building a universal application or even a guide/manual for using current applications.